Randomised trial of telephone counselling to improve participants' adherence to prescribed drugs in a vascular screening trial. Issue 6 (16th July 2020) - Qvist, Ina; Lindholt, Jes S.; Søgaard, Rikke; Lorentzen, Vibeke; Hallas, Jesper; Frost, Lars
Abstract: A total of 1446 participants, 65‐ to 74‐year‐old men diagnosed with abdominal aortic aneurysm (AAA), peripheral arterial disease (PAD) or high blood pressure (HB) in the Viborg Vascular (VIVA) screening trial, were consecutively included and randomised to a telephone counselling (TC) or no TC 3 months after being screened positive. Data from VIVA were linked to data from Danish registers from 2007 to 2016. The primary outcome was a composite outcome of proportion of days covered by statin, antithrombotic drugs and antihypertensive agents and for each specific drug class at 6‐month follow‐up. The same outcomes were assessed at 12 and 60 months and considered secondary outcomes. Outcome measures are reported as risk differences (RD). There were no differences between the groups in relation to the composite of all three drug classes over 6 months of follow‐up, RD = 4.1 (95% CI: −1.0; 9.1). A significant increase in redeemed statin prescriptions was observed in the intervention group at 6 months, RD = 9.8% (CI 95%: 0.5; 19.0). There was no intervention effect observed after 12 and 60 months. TC 3 months after screening improved adherence to statin at 6‐month follow‐up, but had no effect on the composite treatment, statins, antithrombotic or antihypertensive treatment over 60 months of follow‐up.